PENGELOLAAN LINGKUNGAN KELAS DALAM MENCAPAI HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Safitri, Novi; Furqon, F. (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2018)
Behavioristic learning theory states that student learning outcomes are determined by the content of learning and environmental influences. One factor is the classroom environment, the comfortable classroom environment allows students to concentrate. Students spend more time in class than in other school environments. Education in economic subjects is a lifelong learning process, which is beneficial to life. Economic subjects discuss the basic economic concepts that are directly related to everyday life. The main objective of economic subjects is to prepare students with the knowledge necessary to understand the world and make better choices and prepare them to serve as economic actors in the future. The classroom environment on economic subjects will be connected to the teaching and learning process, including the physical and non-physical environments. Learning theory from Albert Bandura known as Social Learning Theory (social learning theory) with the main concept of reciprocal determination, states that there is a constant interaction between environment, behavior and people that influence the learning process that will ultimately affect the learning outcomes obtained. So it can be said that human behavior is the result of continuous interaction between internal factors (behavior, people) and external (environment).